La lenguas nativas del Antiplano peruano-boliviano en el siglo XVI - Espinoza Soriano, Waldemar (2005)
The studyof Chronicles, Dictionaries and Grammars of the XVI century associated with ethnological sources enables Ethnohitory to examine the societty and he daily life of southern, Andean towns. the author proposes a new reading of the origins of Quechua, an outline of the Geographical distribution of the several Anden languages and an explananation of the persistence of the Puquima language until the nieneteeh century in the Bishoprics of la Plata; Cuszco and Areqyuips